2020
DOI: 10.1002/pds.4965
|View full text |Cite
|
Sign up to set email alerts
|

Dual renin‐angiotensin‐aldosterone blockade: Implementation of published research and Dear Doctor letters in ambulatory care: A retrospective observational study using prescription data

Abstract: PurposeThis study aims to assess the implementation of published research, contraindications, and warnings on the prescription of dual renin‐angiotensin‐hormone system (RAS) blockade in ambulatory care in Germany.MethodsCohort study based on health claims data of 6.7 million subjects from 2008 to 2015. Yearly prevalence and incidence for dual RAS blockade with (a) angiotensin‐converting enzyme inhibitors and angiotensin‐receptor blockers (ACEI + ARB) and (b) aliskiren and ACEI or ARB (aliskiren + ACEI/ARB) wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
0
2
0
1
Order By: Relevance
“…Die gleichzeitige Gabe von ACE-Hemmern und ARB kann jedoch zu vermehrten Nebenwirkungen (Hyperkaliämie, Hypotonie, Nierenschädigung) führen und zeigt keinen positiven Effekt auf die Mortalität (QI 23; [ 25 , 26 ]). Zwar sinkt inzwischen die Häufigkeit solcher Doppelverordnungen in Hausarztpraxen, sie tritt aber weiterhin auf [ 27 ].…”
Section: Diskussionunclassified
“…Die gleichzeitige Gabe von ACE-Hemmern und ARB kann jedoch zu vermehrten Nebenwirkungen (Hyperkaliämie, Hypotonie, Nierenschädigung) führen und zeigt keinen positiven Effekt auf die Mortalität (QI 23; [ 25 , 26 ]). Zwar sinkt inzwischen die Häufigkeit solcher Doppelverordnungen in Hausarztpraxen, sie tritt aber weiterhin auf [ 27 ].…”
Section: Diskussionunclassified
“…to reduce these risks [1]. However, the effectiveness of DDLs has been challenged [2][3][4][5], in part due to insufficient quality of warning instructions in DDLs [6]. Furthermore, a Dutch study found that DDLs regarding the risk of hospitalization are less effective than DDLs related to the risk of death or disability [7].…”
Section: Introductionmentioning
confidence: 99%
“…Dear Doctor Letters (DDLs), also known as Direct Healthcare Professional Communications (DHPCs), are paper-based warning letters with the intention of informing physicians about newly detected drug risks and recommendations to reduce these risks [ 1 ]. However, the effectiveness of DDLs has been challenged [ 2 5 ], in part due to insufficient quality of warning instructions in DDLs [ 6 ]. Furthermore, a Dutch study found that DDLs regarding the risk of hospitalization are less effective than DDLs related to the risk of death or disability [ 7 ].…”
Section: Introductionmentioning
confidence: 99%